VALUE ORIENTATIONS, EMOTIONAL INTELLIGENCE AND INTERNATIONAL PEDAGOGICAL INNOVATIONS - Radin, Michael Alexander; Shlat, Natalia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The primary goal of this paper is to portray how the value orientations and priorities can direct us to new pedagogical cores and innovations and leadership. First of all, we will examine how the students’ value orientations and priorities become a pertinent factor in conceiving new teaching practices that enhance the amiable learning atmosphere and guides us to new ideas and leadership. Second of all, we will focus on how value orientations and priorities expand our current knowledge and comprehension of the students’ learning styles and demands and gravitate teachers and students to the concept of emotional intelligence; this then leads students and teachers to new international and interdisciplinary environment(s) and to new teaching and learning practices. In addition, our aim is to address the students’ value orientations and priorities and apply them to steer us to design new learning environment(s) and to the transformational and primal leaderships. Furthermore, our intent is to render how value orientations guide to the emotional intelligence, which then directs to new practices, ideas and innovations. Moreover, we will share specific examples of successful pedagogical innovations that lead to the emotional intelligence and were guided by the students’ value orientations and priorities. Throughout this paper we will remit the following vital question: how do we link the value orientations together with the emotional intelligence and the transformational and primal leaderships?